2011
DOI: 10.1159/000327545
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Thymic Stromal Lymphopoietin Production by Xylene and Exacerbation of Picryl Chloride-Induced Allergic Inflammation in Mice

Abstract: Background: Some chemical compounds in the environment worsen allergic inflammation. In this study, we examined whether organic solvents induce the production of thymic stromal lymphopoietin (TSLP) which elicits Th2-type immune responses. Methods: Organic solvents were painted on the earlobes of BALB/c mice. The expression of TSLP in the ear was determined by ELISA. Results: Xylene and toluene, but not chloroform or ethyl acetate, induced the expression of mRNA for TSLP in the earlobe tissue. Among the aromati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 42 publications
1
25
0
Order By: Relevance
“…TSLP immunostaining revealed the presence of TSLP-producing cells in epithelial tissues. Xylene-induced TSLP production was not reduced in mast cell-deficient mice (34), which demonstrated that mast cells were not a main source of TSLP. Interestingly, xylene-induced TSLP production appeared to be diminished in both TNF-a-knockout mice and IL-4-knockout mice.…”
Section: Dibutyl Phthalate (Dbp)mentioning
confidence: 89%
See 2 more Smart Citations
“…TSLP immunostaining revealed the presence of TSLP-producing cells in epithelial tissues. Xylene-induced TSLP production was not reduced in mast cell-deficient mice (34), which demonstrated that mast cells were not a main source of TSLP. Interestingly, xylene-induced TSLP production appeared to be diminished in both TNF-a-knockout mice and IL-4-knockout mice.…”
Section: Dibutyl Phthalate (Dbp)mentioning
confidence: 89%
“…Xylene and trimethylbenzene are component of paints and glues, and both have been detected at relatively high concentrations in the indoor environment (Table 2), which suggests that exposure to these compounds occurs easily. Xylene was shown to aggravate picryl chroride-induced thickening of the ear and IL-4 production, both of which were attenuated in TSLPRdeficient mice (34), indicating that xylene-induced TSLP affected immune responses. TSLP immunostaining revealed the presence of TSLP-producing cells in epithelial tissues.…”
Section: Dibutyl Phthalate (Dbp)mentioning
confidence: 98%
See 1 more Smart Citation
“…hMPV infection of airway epithelial cells is cytopathic, and the resultant cell injury triggers a series of inflammatory reactions. On the other hand, an unbalanced T helper (Th)1/Th2 immune response to hMPV infection may occur, which would release a series of inflammatory mediators, cytokines, and chemokines, and cause wheezing (21)(22)(23). Studies have shown that TSLP, a newly discovered cytokine, may aggravate excessive The differences between 2 groups were compared using the nonparametric Mann-Whitney 2-sample U test for unpaired data.…”
Section: Discussionmentioning
confidence: 99%
“…Akasaki et al (27) examined the roles of TSLP and IL-33 in acute and chronic allergic rhinitis models, and found that TSLPR-deficient mice showed defective Th2 activation and nasal eosinophilia even after chronic ragweed exposure, which suggested that TSLPR contributes to Th2 responses in chronically allergen-exposed mice. Other experiments in vitro also showed that TSLP can promote Th2 cytokine-mediated inflammation and facilitate production of IL-4, IL-5, IL-13, and tumor necrosis factor-alpha, which can aggravate airway inflammation leading to difficulty in breathing (23,28). In our present study, the plasma levels of TSLP and IL-4 in wheezing children with hMPV infection were significantly higher than those in non-wheezing children with hMPV infection and those in wheezing children with other viral infections.…”
mentioning
confidence: 95%